Ultra Performance Liquid Chromatographic Method for the Determination of Cetirizine Dihydrochloride in Commercial Pharmaceutical Liquid Formulation - Dermis, Saadet (Asian Journal of Chemistry, 2012)
A new ultra performance liquid chromatographic method was developed for the determination of cetirizine hydrochloride in pharmaceutical liquid formulation. The chromatographic separation was achieved on aquity ultra performance liquid chromatographic BEH C18 (100 × 2.1 mm, 1.7 μm) column and a mobile phase consisting of a water:acetonitrile (50:50, v/v). The flow rate was 0.3 mL min-1 and the detection wavelength was 235 nm. The ultra performance liquid chromatographic method shows excellent linearity over a range of 4 μg mL-1 to 28 μg mL-1. The correlation coefficient for the cetirizine hydrochloride the linear regression equation was more than 0.999. The limit of detection and the limit of quantification for cetirizine hydrochloride were found as 0.39 and 1.30 μg mL-1, respectively. This chromatographic method was validated by using validation parameters. The proposed chromatographic method can be applied to the quality control and routine analysis of cetirizine hydrochloride in pharmaceutical liquid formulation.